Coverage control for mobile sensor networks with time-varying communication delays on a closed curve - Qu, Yi; Xu, Haopeng; Song, Cheng; Fan, Yuan (Journal of the Franklin Institute, 2020)
In this paper the coverage problem of a mobile sensor network subject to time-varying communication delays is investigated. Each sensor is required to move along a fixed closed curve. The goal is to minimize a coverage cost function which is defined as the largest response time from the sensor network to any point on the curve. The maximum velocities of the sensors are assumed to be different from each other. This results in different input saturation constraints on the sensors with first-order dynamics. It is shown that even if time-varying communication delays exist, low gain feedback can be also used to design distributed coverage control laws for the mobile sensors. When the sensors’ delays and their derivative are both upper bounded, the sensor network is guaranteed to arrive at the optimal configuration which minimizes the coverage cost function. Moreover, in this work the maximal allowable upper bound on the sensors’ delays can be increased by choosing a lower upper bound on the sensors’ low control gains. Finally, the effectiveness of the proposed coverage control laws is verified by a numerical example.